Removal of HIV DNA by CRISPR from Patient Blood Engrafts in Humanized Mice - Ramona Bella; Rafal Kaminski; Pietro Mancuso; Won-Bin Young; Chen Chen; Rahsan Sariyer; Tracy Fischer; Shohreh Amini; Pasquale Ferrante; Jeffrey M. Jacobson; Fatah Kashanchi; Kamel Khalili (Elsevier, 2018)
We used NOD/SCID mice, also known as NRG, to assess the ability of lentivirus-mediated intravenous delivery of CRISPR in editing the HIV-1 genome from the circulating PBMC engrafts, some of which homed within several animal solid tissues. Lentivirus-mediated delivery of a multiplex of guide RNAs accompanied by Cas9 endonuclease led to the excision of the targeted region of the viral genome positioned within the HIV-1 LTR from the in-vitro-infected human peripheral blood mononuclear cells (PBMCs) embedded in the spleens of NRG mice. Similarly, the treatment of NRG mice harboring PBMC engrafts derived from HIV-1-positive patients with the therapeutic lentivirus eliminated the presence of the viral DNA fragment in the blood, as well as in the spleen, lung, and liver, of the engrafted animals. Sanger sequence analysis of the viral DNA after treatment with the lentiviral vectors expressing Cas9 and gRNAs verified the editing and removal of the proviral DNA fragment from the viral genome at the predicted sites. This proof-of-concept study, for the first time, demonstrates successful excision of the HIV-1 proviral DNA from patient immune cell engrafts in humanized mice upon treatment with lentivirus-expressing CRISPR and causes a decline in the level of replication-competent virus. Keywords: HIV-1, CRISPR/Cas9, gene editing